Revision of the Crematogaster brevis complex in Asia (Hymenoptera: Formicidae) - Hosoishi, Shingo; Ogata, Kazuo (Zootaxa, 2012)
The Crematogaster brevis complex is revised and seven species and one subspecies, including one new species, are recognized.Two species groups are established based on the worker caste. The C. brevis group contains two species: brevis Emery, 1887;and overbecki Viehmeyer, 1916. The C. treubi group contains five species and one subspecies: bouvardi Santschi, 1920. stat.nov.; kojimai sp. nov.; treubi Emery, 1896; treubi apilis Forel, 1913; walshi Forel, 1902; and yappi Forel, 1901. The followingnew synonymies are proposed: C. treubi Emery, 1896 = C. millardi Forel, 1902 = C. treubi vastatrix Forel, 1911. A key to the species based on the worker caste is given. Crematogaster jacobsoni Forel, 1911 is transferred to the subgenus Crematogaster.